Effect of sandblasting on the tensile bond strength of two permanent silicone soft liners to the denture base - Soheil Khakbaz Baboli; Kamran Amirian Chaijan; Maryam Rezaei Dastjerdi; Hemmat Gholinia (Babol University of Medical Sciences, 2019)
Introduction: Soft liners are materials used in removable dental prostheses to maintain the health of inflamed mucous membranes. The materials bond strength to acrylic bases can be modified by several methods; One of which includes sandblasting. The aim of this study is to investigate the effect of sandblasting on the tensile bond strength(TBS) of two permanent silicone soft liners. Material & Methods: 36 dumbbell-shaped heat-cured polymethylmethacrylate acrylic specimens were fabricated in denture flasks with a length of 75 mm, width of 12 mm and a thickness of 7 mm in the thinnest section. 3 mm of the material of all specimens was cut using a low-speed diamond saw with water cooling. Then according to the surface treatment and sofliners, the specimens were divided into four groups: no surface treatment with mollosil softliner, no surface treatment with GC softliner,  sandblasting with 50 μm Al2O3 particles and then using  mollosil soft liner and sandblasting with 50 μm Al2O3 particles and  then using GC soft liner. After polymerization of all specimens, TBS was evaluated with universal testing machine at a crosshead speed of 5 mm/min until failure. Finally, two-way ANOVA and independent T-test were used to analyzing the data. Results: The mean of TBS in the groups of sandblasting was significantly higher than other group and the mean of TBS  in the group of mollosil was higher than GC group with or without sandblasting. (p=0.001) Conclusion: Sandblasting increases the TBS of silicone soft liners to the acrylic bases; moreover, Mollosil softliners are more tenacious compared to GC.